1975
DOI: 10.1021/bi00673a005
|View full text |Cite
|
Sign up to set email alerts
|

Calorimetric analysis of aspartate transcarbamylase from Escherichia coli. Binding of cytosine 5'-triphosphate and adenosine 5'-triphosphate

Abstract: The binding of CTP and ATP to aspartate transcarbamylase at pH 7.8 and 8.5 at 25 degrees has been investigated by equilibrium dialysis and flow microcalorimetry. The binding isotherms for CTP at both pH 7.8 and 8.5 and ATP AT PH 8.5 can be fit by a model which assumes three tight, three moderately tight, and six weak binding sites. The binding isotherms for ATP at pH 7.8 are best fit by a model which assumes six tight and six weaker sites. Both finite differenceH binding and finite differenceS binding are nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
21
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 40 publications
6
21
0
Order By: Relevance
“…The half-saturating concentration for ATP activation was 0.8 mM, whereas CTP-induced inhibition required levels that were decreased by a factor of -5 (0.15 mM). This weaker binding of ATP has been described by others (19,20) and would explain the dominance of CTP inhibition over ATP activation. The nature of this competitive advantage for CTP can be described in a slightly different manner by evaluating competitive saturation curves (data not shown).…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…The half-saturating concentration for ATP activation was 0.8 mM, whereas CTP-induced inhibition required levels that were decreased by a factor of -5 (0.15 mM). This weaker binding of ATP has been described by others (19,20) and would explain the dominance of CTP inhibition over ATP activation. The nature of this competitive advantage for CTP can be described in a slightly different manner by evaluating competitive saturation curves (data not shown).…”
Section: Resultssupporting
confidence: 68%
“…These allosteric controls have been promoted for their inherent logic in balancing endogenous purine and pyrimidine nucleotide pools; however, there has always been a quantitative paradox relative to the incomplete inhibition by CTP (10, 14, 15). In addition, it appears that there is discrete heterogeneity in CTP binding as half of the allosteric sites are capable of providing for high-affinity binding of CTP whereas three additional, lowaffinity sites have been identified in some studies (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also suggested that the pH‐dependent shift in the Asp saturation curve is largely because of changes involving intersubunit salt bridges. Finally, a detailed study of the Bohr effect in ATCase was performed using calorimetry, potentiometry, and spectrophotometry to analyze the coupling between the binding of protons and substrate analogues 15, 17. This work identified two residues with p K a values of 6.3 and a third residue with a pK a of 9.1 that play a critical role in the Bohr effect of ATCase 18…”
Section: Introductionmentioning
confidence: 99%
“…pK values of groups involved in binding and/or catalysis have been derived from the pH dependence of the kinetic parameters of c 3 (Leger and Hervé, 1988;Turnbull et al, 1992), and a model involving three active site residues has been proposed (Turnbull et al, 1992). Allewell et al (1975) showed that nucleoside triphosphate binding is linked to proton binding, and in a series of subsequent papers they defined linkages between proton binding and binding of substrates, competitive inhibitors, and nucleotides and the assembly reaction (Knier and Allewell, 1978;Allewell et al, 1979;Burz and Allewell, 1982;McCarthy and Allewell, 1983). Computer modeling indicates that these linkages result from large changes in the pK a values of groups widely distributed throughout the molecule (Glackin et al, 1989(Glackin et al, , 1991.…”
mentioning
confidence: 99%